Rolling stones. From the jessuit missions to Buenos Aires - Daniel Schávelzon (Antiguos Jesuitas en Iberoamérica, 2018)
The study of stones and rubble in a small section of the already totally artificial coast of the city of Buenos Aires, showed the presence of two recently arrived and very worn stones. Due to its reddish coloration, its geological composition and the evidence of manual carving, it was assumed that it came from the Misiones area and that it must have been part of buildings. We do not know where they come from, how that enor-mous trip was made in distance and in centuries, but they arrived recently and stayed over de muddy coast. Finally it is just a curiosity, there must be hundreds of Jesuit buildings destroyed in time and whose stones fell into the water; these two, curiously, were visible at a great distance, and shortly before leaving the ocean and lost forever.